Công nghệ ATM và ứng dụng trong mạng cục bộ LAN - Lợi, Vũ Duy (Journal of Computer Science and Cybernetics, 2016)
In this paper we present some selected important features of the Asynchronous Transfer Mode ATM and its application as backbone network technology used in Local Area Network LAN. Various standardized methods used to implement ATM-based LAN are mentioned. We consider the LAN Emulation according to ATM Forum in detail. The ATM-based network interconnection system COSY (Cell Oriented system) which the author was working for is illustrated as an example for implementing an ATM-based LAN